THE UNSOLVED FUNDAMENTAL PROBLEMS OF GENERAL MICROBIOLOGY - Maryin V.A.; Kharitonov D.V.; Kharitonova I.V. (Техника и технология пищевых производств)
According to the authors three fundamental Laws of Nature : 1. The Law of exponential growth of microorganisms; 2. The Law of direct proportionality which is unknown now to the most of microbiologists; 3. The Law of exponential reduction in the course of time of survived passive (latent) microorganisms in biological samples (e.g. in dry bacterial concentrates) under their permanent storage conditions making cell growth impossible are the basis of general microbiology. All microbiologists recognize only the First law out of the three Laws listed. The remaining two Laws are not recognized officially so far. This work substantiates the necessity to recognize all three Laws of Nature as only the three make the fundamental base of general microbiology. Living cells of microorganism growing culture comprise active (growing) and passive (latent) cells: (X gen.)o = (Xact.)o + (X pas.)o. Only active cells are growing in the exponentially growing culture. Passive cells are not growing and therefore the known equation of exponential growth of all living cells of the culture (Xgen.)t = (Xgen.)o · (Xpas.) · e μt is not really observed: (Xgen)t = (Xact.)o · e μt + (Xpas.)o # [(Xact.)o] · e μt. A new equation of exponential growth of all living cells of the culture considering a continuous passivation of active cells has been derived: (Xgen.)t = (Xgen.)o · e αμ · t, where μ = const., αt means the part of active cells in the cultural media. In the exponentially growing culture the value αt is gradually reducing with time and so the natural growth of the culture is not and can’t be strictly exponential. The necessity to introduce the proposed clarifications and changes in the Law of exponential growth of microorganisms is stipulated by the earlier unknown phenomenon of passivation (formation of latent forms) of active cells of exponentially growing culture of microorganisms during the whole period of its growth. The Law of direct proportionality – the basic law of microorganisms’ vital activity – has been considered in brief. According to the Law of direct proportionality the increase of microorganism concentration in the cultural medium is directly proportional to a simultaneous increase of metabolite ∆Mt concentration and a simultaneous decrease of substrate (-∆St ) concentration in it as well as a simultaneous increase of titratable acidity of the cultural medium ∆At (under lactic acid bacteria cultivation): ∆Xt [CFU/ml] = Kc · (–∆St )[g/l] = KM· · ∆At [ oT]. (Formulated by Maryin V.A. in 2002. Experimentally substantiated by him in 2003). Newly formulated and substantiated in detail has been unrecognized now by microbiologists the Third Fundamental Law of general microbiology mentioned above: (Xpas.)t = (Xpas.)o · e – t . Microbiologists’ attention is attracted to the discovery of the new phase of microorganisms’ growth – the phase of linear growth at All-Russian Dairy Research Institute, (Mary’in V.A. 2002).